The Reactions of Generation Y to the Use of Social Networking Websites in Personnel Selection in China - Li, Chujun (2017)
This study examines the reactions of Generation Y to the use of social networking websites (SNW) in personnel selection of in China. In particular, the roles of perceived privacy invasion, fairness perceptions and intentions of job pursuit of participants and the influence of the presence of justifications for SNW screening on participants’ reactions are examined. Because using SNW to screen and select applicants is increasingly popular in organisations, it seems to be helpful to study the reactions of Generation Y to the use of this selection tool when they are in the scenario of being applicants. Organisations can decide whether to use SNW as a selection tool or not and realise how to influence the applicants’ reactions to this selection tool according to the results of current study.